KERAGAAN DAN SELEKSI GALUR F5 GANDUM (OASIS X HP1744) DI DATARAN TINGGI - Yushi Mardhiana (Universitas Islam Kadiri, 2016)
The purpose of this research was to select F5of wheat lines (Oasis x HP1744) that have high yield potential in high altitude agroecosystem. This research was conducted in July to November 2013 in the experimental field of Ornamental Research Station (BALITHI) Cipanas (±1100 m asl, ±21 oC). There were 78 lines of F5 wheat from Oasis x HP1744 and 6 check varieties arranged by augmented design. The results showed that the lines were significantly different in total number of tiller, number of productive tiller, spike lenght, spike number, spike density, empty floret percentage, grain filling rate, grainnumber of main spike, grain weight of main spike, grainnumber per plant, and grain weight per plant. The highest heritability was estimated for spike density (93.8). The results of path analysis showed that grain number of main spike and grain weight of main spike had high values of direct effect on grain weight per plant. The direct selection by grain weight per plant increased the yield potential by 14.6% and reduced the empty floret percentage by 26.8%. The selection by grain weight of main spike increased the yield potential by 11.3% and reduced the empty floret percentage by 22.3%.